CD34+ Circulating Progenitor Cells after Different Training Programs - Niño, O.; Balague, N.; Aragones, D.; Blasi, J.; Alamo, J.M.; Corral, L.; Javierre, C.; Miguel, M.; Viscor, G.; Ventura, J. L. (International Journal of Sports Medicine, 2015)
Circulating progenitor cells (CPC) are bone marrow-derived cells that are mobilized into the circulation. While exercise is a powerful mediator of hematopoiesis, CPC levels increase, and reports of their activation after different types of exercise are contradictory. Moreover, few studies have compared the possible effects of different training programs on CPC concentrations. 43 physically active healthy male subjects (age 22±2.4 years) were assigned to 4 different training groups: aerobic, resistance, mixed and control. Except for the control group, all participants trained for 6 weeks. Peripheral blood samples were collected through an antecubital vein, and CPC CD34+ was analyzed on different days: pre-training, post-training, and 3 weeks after finishing the training period. While no significant differences in CPC were observed either within or between the different training groups, there was a tendency towards higher values post-training and large intra- and intergroup dispersion. We detected an inverse linear relationship between pre-training values and % of CPC changes post-training (p<0.001). In the CPC values 3 weeks after training this inverse relationship was maintained, though to a lower extent (p<0.001). No changes in CPC CD34+ were detected after 6 weeks of different training groups, or after 3 weeks of follow-up.
Keywords: stem cells; physical activity; training